Perancangan Sistem Pendukung Keputusan Dalam Pemilihan Ketua Kelas Mahasiswa Kelas 07TPLE004 Dengan Menggunakan SAW, WP Dan TOPSIS - Asep Muhammad Junaedi; Asep Sucipto Indra Sukma; Juhaendi; Muhammad Fauzan Sabana; Perani Rosyani (CV. Multi Kreasi Media, 2023)
In the class of a class representative it is very mandatory in the selection of candidates they must introduce themselves and also register from the many students who have their respective achievements and potential in the selection of class leaders in this student is still said to be uneven, in the selection of class leaders it is still subjective because students who are said to be quite famous can become class leaders, therefore students will randomly select candidates for class leader 07TPLE004 so that they can be said to be fair in the election. To deal with this problem, the author makes a problem-solving solution quickly and is able to know the highest and lowest scores on the assessment using SPK, it will be able to make the election fair and there will be no students who feel cheated by the election the author uses SAW, WP and TOPSIS methods where the candidates for class president are Fauzan Sabana, Asep Sucipto, Asep Junaedi, Juhaendi, and Fathul Ghina.